2015
DOI: 10.2147/dddt.s81303
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hydroxychloroquine maculopathy after cessation of treatment: an optical coherence tomography and multifocal electroretinography study

Abstract: ObjectiveThis study was conducted to evaluate the macular status of patients treated with hydroxychloroquine before and after cessation of treatment.MethodsForty-two patients with systemic lupus erythematosus underwent ocular examination based on visual acuity evaluation, optical coherence tomography retinal thickness measurements, and multifocal electroretinography (mfERG) records at first visit. The tests were repeated 6 months after treatment withdrawal and compared to the findings at their first visit.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…These data are consistent with previous reports in the literature,24,27,28 and only one study found an increased latency without reduction in amplitude 29…”
Section: Discussionsupporting
confidence: 93%
“…These data are consistent with previous reports in the literature,24,27,28 and only one study found an increased latency without reduction in amplitude 29…”
Section: Discussionsupporting
confidence: 93%
“…Retinopathy and maculopathy are widely known complications of hydroxychloroquine treatment, although inflammatory pseudotumor has never been described in this setting. Although visual loss may be irreversible and even worsen after suspending treatment with hydroxychloroquine, this is more likely if high doses of hydroxychloroquine are used for more than 5 years or if there is impaired renal or liver function . Although our patient had been treated with hydroxychloroquine for 10 years, the daily doses were below 6, 5 mg/kg, which are associated with very low risk of retinopathy.…”
Section: Discussionmentioning
confidence: 77%
“…25,59 One longitudinal study evaluated visual acuity, SD-OCT imaging data and mfERG of patients on HCQ, and 6 months following drug cessation finding improved visual acuity and mfERG responses, but not OCT appearances. 61 A further study evaluating only SD-OCT imaging characteristics before and for 4 years after drug cessation in 11 patients with HCQ retinopathy found that if HCQ is stopped before RPE damage, progression of disease on SD-OCT is limited to the first year and diffuse in distribution without parafoveal localisation. 39 There is some evidence that preservation of the external limiting membrane is a favourable prognostic sign in HCQ retinopathy.…”
Section: Hydroxychloroquine Drug Cessationmentioning
confidence: 99%
“…60 One study identified improvement of visual function in HCQ retinopathy following drug cessation, but no improvement in structural parameters. 61 A key recent finding was the identification of variable distributions of disease in HCQ/CQ retinopathy on the basis of race. 62 Patients of European descent exhibit a classic parafoveal pattern (2-6 degrees from the fovea) of structural and functional deficits, were more likely to manifest an extramacular or pericentral (more than 8 degrees from the fovea) pattern of disease in the early stages with structural and functional abnormalities identified near the vascular arcades.…”
Section: Clinical Featuresmentioning
confidence: 99%